Ansiedad y dependencia a la nicotina en estudiantes de medicina humana de la Universidad Nacional de Loja - Sánchez Quezada, Bryan Andrés (2022)
Anxiety is one of the frequent disorders that affect the student population that, together with nicotine dependence, leads to problems that normally go unnoticed by teachers and family members. The purpose of this research was to determine the degree of anxiety, to know the degree of nicotine dependence according to age group and sex, and to establish the relationship between these variables, in medical students at the National University of Loja with a quantitative cross-sectional approach, with a sample of 70 students who met the inclusion and exclusion criteria, to whom the Hamilton and Fagerstrom test was applied, obtaining as a result that the age group between 22 and 25 years of age presented the greater number of cases of mild anxiety, 71.43% (n=50) aged between 22 to 25 years presented mild anxiety, predominantly female with 38.57% (n=27). The age group between 22 and 25 years of age showed very low dependence on nicotine with 47.14.71% (n=33), especially in men with 28.57% (n=20). Regarding the relationship between variables, statistical significance was found ("p" value = 0.008), and shows an association between anxiety and nicotine dependence. Concluding that women are the most affected, between 22 to 25 years of age due to mild anxiety and men of the same age group due to very low dependence on nicotine